Learning Modules. Enhancing the science-policy-investment linkages and decision support for climate-smart agriculture planning - Trautman, Sabrina; Remans, Roseline; Zornetzer, Heather; Nowak, Andreea C.; Neely, Constance; Cramer, Laura K.; Gosling, Amanda; Chevallier, Romy; Rosenstock, Todd S. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Enhancing the Science-Policy-Investment Linkages and Decision Support for Climate-Smart Agriculture Planning learning materials highlights and expands upon key methods, tools, and actions to actively strengthen decision contexts in scaling climate-smart agriculture in Africa. These learning materials and content are built to include both technical skill building resources as well as process and approach guidance to help uncover more equitable, holistic, and resilient pathways to increase climate-resilience in our food and agricultural systems. The materials include insights on approaches and tools for key stakeholders to make informed decisions more broadly related to adaptation and implementing climate-smart agriculture. The learning Modules are aimed to be used by the multiple institutions and partnerships supported by the Accelerating Impacts for CGIAR Research for Africa (AICCRA) project to support decision making and serve as foundational concepts, approaches, tools and soft-skills development. Key stakeholders that can gain learning value from the materials include policy actors, small- and medium-sized agri-businesses, climate action and agri-food system innovators, climate adaptation researchers for development, field and producer technical extension support providers, and farmer association representatives and supporting advisors. The learning is structured into one Foundational and four key Modules which are relevant to the different stages of the adaptation cycle including: i) Co-learning, stakeholder relationships and working in systems; ii) Evidence and climate change decision and policy processes; iii) Approaches and tools for planning and assessment; and iv) Monitoring and evaluation of climate-smart agriculture investments.